(untitled) (Proceedings of International Conference on Special Education, 2015)
Deaf students and sign-language-teaching teachers in 81 special education schools at all levels are selected for sign language usage survey. The results show that: firstly, teachers have the higher proportion of using “Chinese Sign Language” and “two kinds of sign language both” than deaf students, but lower proportion of using “local sign language”. Secondly, the level of teachers using "Chinese sign language" and "local sign language" is significantly higher than the deaf students. Thirdly, with regard to the intelligibility of teachers’ usage of sign language in the teaching, teachers have higher expectation than the deaf students’ understanding. Furthermore, because of the differences of using sign language between teachers and students as well as deaf adults out of school, it is kind of difficult to teach in special education school and communicate with the deaf adults. Finally, most teachers and students in special education schools hope to develop a general sign language that all the deaf can understand. Comparatively speaking，the voice of teachers is louder than others.